Estudios recientes de metales pesados en peces: Una revisión bibliográfica con énfasis en Perú - Morales Rojas, Eli (2022)
Heavy metals cause harmful effects on human health through the food chain. In this sense, the objective of this research was to analyze the advances in the scientific production of heavy metals in fish in the countries of Peru, Bolivia and Chile, by means of a bibliographic review. The search was carried out in the Scopus database from 2000 to May 2022, and an analysis was made of the selected articles according to the place of study. VOSviewer software (a tool for constructing and visualizing bibliometric networks) was also used to generate coauthorship networks. The results indicate that studies on heavy metals began to stand out during the years 2012, 2019. The author with the highest participation was Custodio. Finally, it is concluded that research is scarce and these topics should be addressed with greater emphasis according to each state, given that in many cases the values exceed the established norms